(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Upon completing my doctoral qualifying exams in the late 1960s, I went to Berlin to commence research on my dissertation. My thesis adviser arranged for me to meet Jakob Taubes (1923-1983), then teaching at the Freie Universität zu Berlin. At our very first meeting, almost immediately after I had crossed the threshold of his home tucked in a bucolic corner of the city, Taubes asked me what I thought of Shabbatai Tzvi, the antinomian pseudo-Messiah. Taken aback by the question, I mumbled some inane academic reply, assuming it was the beginning of a second round of my doctoral orals. My reply was met with silence. Although the conversation soon resumed with a cordial discussion of my research project, I was soon to realize that with his startling introductory query, Taubes did not intend to probe my scholarly credentials. Rather he sought to alert me to the existential and religious questions that preoccupied him as a Jew in self-imposed exile in Berlin.